The Social dimensions of climate change learning module. (World Bank, 2009)
The Social Dimensions of Climate Change (SDCC) Learning Module aims to increase understanding of vulnerability to climate change and invites users to explore how a social perspective can inform climate change policy at the global, national and sub-national levels. This participatory training encourages knowledge exchange among development practitioners on the full range of complex social responses to climate change. -- [p.3]